F-Commerce in Bangladesh: “Venit, Vidit, Vicit” - Zabeen, Mashruha; Ara, Husna; Sarwar, Nafish (Universiti Sains Malaysia, 2013)
The term “F-Commerce” is a neologistic portmanteau of Facebook and Commerce; referring to a type of marketing channel which facilitates - advertising, auctioning, purchasing and selling of any products (goods and/or services) through the social media network Facebook. The vast popularity of Facebook enabled F-Commerce platform to rapidly enhance the shopping tendency of its users with in a very shorter period of time. Literally it just came and concurred the market; as in Latin Venit, Vidit, Vicit. Objective of this exploratory research is to observe the adoption of F-Commerce in Bangladeshi context and identify its potential implications. An anthology of group discussions with the consumers and thorough case studies on the Bangladeshi f-traders were carried out during the month of June-July 2013. And crosschecking the group discussions with the Internet reviews permitted the researchers to ensure the validity of the findings.